An eight-year retrospective analysis of antenatal screening results for syphilis: is it still cost effective? - Tugba Ensari; Ayse Kirbas; Ayse Seval Ozgu-Erdinc; Sibel Gokay Saygan; Salim Erkaya; Dilek Uygur; Nuri Danisman (Journal of Infection in Developing Countries)
Introduction: This study aimed to document the prevalence of syphilis among pregnant women in Turkey. Methodology: In this retrospective cohort study, a total of 63,276 sera obtained between January 2007 and June 2014 from women who were routinely screened for syphilis as a part of antenatal care at a tertiary referral hospital in Turkey were analyzed. Serological screening was done with the rapid plasma reagin (RPR) test on venous blood samples. Treponema pallidum hemagglutination assay (TPHA) was the confirmation test for the diagnosis of syphilis in patients who had positive results in the screening test. Results: Between 2007 and the first six months of 2014, 41 RPR+ and only five confirmed syphilis-positive patients were determined. The syphilis seroprevalence rate was 0.0648%. Within these years, there was no case of congenital syphilis detected in the hospital. Conclusion: As there is evidence of effective screening of syphilis contributing to the effective treatment and prevention of adverse outcomes, routine antenatal screening of syphilis is recommended. The rationale depends on the consideration of the serious results of not treating the disease and the cost effectiveness of screening.